Characterization of the major promoter for the plasmid-encoded sucrose genes scrY, scrA, and scrB. - Cowan, P J (1991)
Sucrose genes from a Salmonella thompson plasmid were cloned in Escherichia coli K-12. A physical map and a genetic map of the genes were constructed, revealing strong homology with the scr regulon from the Salmonella typhimurium plasmid pUR400. Two promoters were examined after being subcloned into transcriptional fusion vectors. Primer extension analysis and site-directed mutagenesis were used to identify the precise location of the promoter of scrY, scrA, and scrB. Transcription from this promoter was regulated over a 1,000-fold range by the combined effects of ScrR-mediated repression and catabolite repression. A putative cyclic AMP receptor protein binding site centered 72.5 bp upstream of the start point of transcription of scrY appeared to be essential for full activity of the scrY promoter. Transcription from the putative scrK promoter was far less sensitive to repression by ScrR. In ScrR+ cells, readthrough transcription from the putative scrK promoter into scrY accounted for less than 10% of scrY expression.